Characterization of a novel liquid fiducial marker for multimodal image guidance in stereotactic body radiotherapy of prostate cancer. Issue 5 (15th April 2018) - De Roover, Robin; Crijns, Wouter; Poels, Kenneth; Peeters, Ronald; Draulans, Cédric; Haustermans, Karin; Depuydt, Tom
Abstract : Purpose: Liquid fiducial markers have shown to be a promising alternative to solid gold markers in terms of imaging artifact reduction, patient comfort, and compatibility with different imaging modalities. This study aims to investigate the performance of the novel BioXmark ® liquid marker for state‐of‐the‐art multimodal imaging used in prostate cancer (PCa) radiotherapy, encompassing kV CT/CBCT, multiparametric MRI, and kV x‐ray imaging. In addition, automatic detection of the liquid markers in x‐ray imaging for prostate motion monitoring during treatment was investigated. Methods: A total of eight BioXmark ® liquid markers with varying volumes (range 5–300 μL) were casted on a square grid into a gelatin phantom insert. A cylindrical gold marker (QLRAD, length = 7 mm, Ø = 1 mm) was inserted for reference. Liquid marker visibility and streaking artifacts in CT/CBCT imaging were evaluated by placing the gelatin phantom into a CIRS anthropomorphic phantom. Relevant MRI characteristics such as the T2 and T1 relaxation times, the ADC value, and the relative proton density ( ρ H ) were quantified by placing the gelatin phantom insert next to a T1MES mapping phantom and a water‐filled syringe for reference. Ex vivo multiparametric MRI images were acquired by placing the gelatin phantom next to a resected prostate specimen. Anterior–posterior x‐ray projection images were obtained by placing the gelatin phantom insert on top of an anthropomorphic pelvic phantom with internal pelvic bony structures and were acquired for five positions relative to the bony anatomy and 24 clinically relevant x‐ray exposure settings. To quantify individual automatic marker detection, single markers were artificially isolated in the x‐ray images using postprocessing. Results: Markers of all sizes were clearly visible on CT and CBCT images with only the largest marker volumes (100–300 μL) displaying artifacts similar in size to the gold fiducial marker. Artifact size increased with increasing liquid marker volume. Liquid markers displayed good contrast in ex vivo T1‐weighted and ρ H ‐weighted images. The markers were not visible in the ex vivo T2‐weighted image. The liquid markers induced a chemical shift artifact in the obtained ADC‐map. Automated detection in x‐ray imaging was feasible with high detection success (four of five positions) for marker volumes in the range of 25–200 μL. None of the liquid markers were detected successfully when superimposed on a bony edge, independent of their size. Conclusions: This study is the first to show the compatibility of BioXmark ® liquid markers with multimodal image‐guided radiotherapy for PCa. Compared to a solid gold marker, they had favorable results in both visibility and induced imaging artifacts. Liquid marker visibility in MRI imaging of the prostate does not solely depend on the low ρ H value (not visible on T2‐weighted image) but is also influenced by its relaxation times. Automated marker detection in x‐ray images was feasible but better adapted marker detection algorithms are necessary for marker localization in the presence of bony edges. Hence, the liquid marker provides a minimally invasive (fine needles) and highly applicable alternative to current solid gold markers for multimodal image‐guided prostate radiotherapy treatments.